2021
DOI: 10.5539/ibr.v14n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Do Performance Goals and Development, Feedback and Recognition, and a Climate of Trust Improve Employee Engagement in Small Businesses in the United States?

Abstract: Small businesses are the predominant contributors to the U.S. economy, yet they face many challenges to remain competitive and sustainable. There are several reasons a small business could fail, including a lack of human resources, limited financial resources, competition, technological advancements, disaster, and globalization. Improving employee performance by getting them engaged and productive in their work is an issue that cannot be overlooked for small businesses to function and remain competitive. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
1
8
0
1
Order By: Relevance
“…On the other hand, emotional intelligence (i.e., self-emotion appraisal, others' emotion appraisal, and regulation of emotion), self-esteem, locus of control, decision authority, and workload were not significantly associated with work engagement. The results are consistent with previous empirical studies on emotional intelligence [56][57][58], skill utilization [63], and recognition [70,71]. These results are also consistent with the JD-R model, which postulates that individual and organizational resources are drivers of work engagement [72].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, emotional intelligence (i.e., self-emotion appraisal, others' emotion appraisal, and regulation of emotion), self-esteem, locus of control, decision authority, and workload were not significantly associated with work engagement. The results are consistent with previous empirical studies on emotional intelligence [56][57][58], skill utilization [63], and recognition [70,71]. These results are also consistent with the JD-R model, which postulates that individual and organizational resources are drivers of work engagement [72].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, recognition is a socio-emotional reward that refers to the esteem received from significant others at work (e.g., colleagues, supervisors) and appreciation received related to achievement (e.g., positive feedback) [69]. It was established that recognition was associated with higher work engagement [70,71], as well as lower intention to quit [68] Individual and organizational characteristics have both been shown to be associated with work engagement when hindered and facilitated working from home during the COVID-19 pandemic [29]. However, we were unable to locate any study that specifically taps into the possible moderating role of work or individual characteristics (both important resources) on the relationship between teleworking, work engagement, and intention to quit since the start of the pandemic.…”
Section: Effects Of Individual and Organizational Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on conservation of resources (COR) theory [35], teleworking could help to prevent a cycle of loss (i.e., a loss spiral) by influencing other work organization conditions and, ultimately, their effects on work engagement and the intention to quit. Indeed, it has been shown that work organization conditions are linked to WE [36][37][38][39] and IQ [40][41][42][43]. We also know from a previous study that teleworking is linked to lower WE and higher IQ through its impact on WE [9].…”
Section: Theoretical Modelmentioning
confidence: 88%
“…Although employee engagement has both enjoyed and endured several definitions over the years (Tate, Lartey, & Randall, 2021), it is defined by Shuck and Wollard (2010) as "an individual employee"s cognitive, emotional, and behavioral state directed toward desired organizational outcomes" (p. 103). According to Kim, Kolb, and Kim (2013), "engagement might be viewed as a proactive and fundamental approach to organizational performance and sustainability" (p. 249).…”
Section: Employee Engagementmentioning
confidence: 99%